Kovergensi IFRS dan Tingkat Konservatisme Akuntansi di Indonesia - Prayanthi, Ika; Pantow, Lyvin Henry (Jurnal Ilmiah Akuntansi dan Bisnis, 2018)
This study aims to measure whether there is a significant difference between the level of accounting conservatism before and after the IFRS convergence. The research method used is a comparative method using paired t test. The sample in this study consists of 600 observational data from a total of 100 companies. The results show that although there is a difference between the conservatism level before and after the convergence period but the difference is not significant (0.676> 0.05). This study answers so many assumptions of various business actors on the suspicion that when Indonesia decided to change the direction of GAAP to IFRS the level of conservatism will be much different. The IFRS principle no longer emphasizes conservative accounting, but IFRS emphasizes the principle of prudence which means the corporate management function responsible for preparing the financial statements is carried out with caution. With the implementation of IFRS, the principle of conservatism does not disappear completely so its still reduce the conflicts of bondholders and shareholders related to dividends. Keywords : Conservatisme, IFRS convergency